30.9k views
5 votes
How do I solve: -2 = 4 (3x - 2) - 6

User Ehxor
by
5.5k points

1 Answer

7 votes

Hello!

The first step is to remove the parenthesis of the equation. To do it, we have to multiply the value inside of it by 4, look:


\begin{gathered} -2=4(3x-2)-6 \\ -2=12x-8-6 \end{gathered}

Now, let's group the similar terms:


\begin{gathered} -2=12x-8-6 \\ -2=12x-14 \\ -2+14=12x \\ 12=12x \\ \\ x=(12)/(12) \\ \\ \boxed{x=1} \end{gathered}

Note:

As I wrote -14 in the other side of the equation, the signal has changed to +.

Answer:

x = 1.

User Jdessey
by
4.5k points